2013
DOI: 10.1088/0953-8984/25/21/215401
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced structural phase transition and equation of state of LiTaO3

Abstract: Using in situ high-pressure x-ray diffraction and ab initio techniques, a high-pressure structure of LiTaO3 has been determined to be an orthorhombic phase with the space group Pnma. At ambient temperature, the transition pressure from the R3c phase (the ordinary phase at ambient pressure and temperature) to the Pnma phase is about 33.0 GPa and the phase transition is reversible. This phase transition can be reproduced qualitatively by ab initio calculations, but with a lower transition pressure of 19.9 GPa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…LiTaO 3 has a trigonal structure that belongs to the R 3 c space group, whereas NCM811 has a hexagonal unit cell belonging to the R 3 ̅m space group . The unit cell of LiTaO 3 is composed of face-shared LiO 6 and TaO 6 octahedra, with each Li and Ta atom bonded to six oxygen atoms . In contrast, in the NCM811 unit cell, different numbers of Ni (20), Co (2), and Mn (2) atoms occupy TM sites surrounded by oxygen atoms, resulting in a Ni mole fraction of 0.833.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LiTaO 3 has a trigonal structure that belongs to the R 3 c space group, whereas NCM811 has a hexagonal unit cell belonging to the R 3 ̅m space group . The unit cell of LiTaO 3 is composed of face-shared LiO 6 and TaO 6 octahedra, with each Li and Ta atom bonded to six oxygen atoms . In contrast, in the NCM811 unit cell, different numbers of Ni (20), Co (2), and Mn (2) atoms occupy TM sites surrounded by oxygen atoms, resulting in a Ni mole fraction of 0.833.…”
Section: Resultsmentioning
confidence: 99%
“…38 The unit cell of LiTaO 3 is composed of face-shared LiO 6 and TaO 6 octahedra, with each Li and Ta atom bonded to six oxygen atoms. 39 In contrast, in the NCM811 unit cell, different numbers of Ni (20), Co (2), and Mn (2) atoms occupy TM sites surrounded by oxygen atoms, resulting in a Ni mole fraction of 0.833. After full relaxations of the unit cells, (012) and (1̅ 10) surfaces of LiTaO 3 and NCM811, respectively, were cleaved (Figure 3a,b, respectively).…”
Section: ■ Experimental Detailsmentioning
confidence: 99%
“…The phase was found to be the orthorhombic perovskite structure (Pnma). 16 For comparison, in Fig. 5, we show x-ray diffraction patterns at selected pressures for both LT and LMT.…”
Section: Rhombohedral Litaomentioning
confidence: 99%
“…Xiang et al 16 reported K o ¼ 116 GPa and K o 0 ¼ 6.6 for LT based on a Birch-Murnaghan equation of state fit. The slightly larger K o reported by Xiang et al 16 may be associated with the stiffer pressure transmitting medium (silicon oil) used in those experiments.…”
Section: E Thermal Factorsmentioning
confidence: 99%
See 1 more Smart Citation